1990
DOI: 10.1093/intimm/2.7.669
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a cDNA encoding the human interleukin 4 receptor

Abstract: Using the mouse interleukin 4 (IL-4) receptor cDNA as a probe, we isolated a cDNA encoding the human IL-4 receptor (hIL-4 receptor) from a multifactor-responsive human myeloid cell line, TF1. The cDNA encodes for an open reading frame of 825 amino acids including a signal sequence (25 amino acids), the external domain (207 amino acids), a transmembrane domain (24 amino acids), and a large cytoplasmic domain (569 amino acids). The human IL-4 receptor has a 65% identity with the mouse IL-4 receptor at the nuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 0 publications
0
52
0
2
Order By: Relevance
“…Amino acid sequence analysis of the purified IL4-BP established the N-terminal sequence GNMKLQ. Thus, the mature protein starts two residues earlier than originally proposed (Idzerda et al, 1990;Galizzi et al, 1990).…”
Section: Cho Cellsmentioning
confidence: 77%
See 1 more Smart Citation
“…Amino acid sequence analysis of the purified IL4-BP established the N-terminal sequence GNMKLQ. Thus, the mature protein starts two residues earlier than originally proposed (Idzerda et al, 1990;Galizzi et al, 1990).…”
Section: Cho Cellsmentioning
confidence: 77%
“…Amino acid residues in all IL4-BP variants are numbered as in the original cloning papers (Idzerda et al, 1990;Galizzi et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…At present, only one IL-4 receptor molecule is fully charact.erized, comprising a. single polypeptide chain of ~ 800 amino acid residues (Mosley et al, 1989;Galizzi et al, 1990;Harada et al, 1990;Idzerda et al, 1990). It occurs at the relatively low flgure of 150 to 2500 molecules per target cell (CabriJlat et al, 1987;Park et al, 1987).…”
mentioning
confidence: 99%
“…Human and mouse IL-4 receptors show a broad distribution on hematopoietic and non-hematopoietic cells , Lowenthal, et al, 1988, generally expressed at low levels (20-4000 receptors per cell).The IL-4R cDNAwas cloned from the mouse cytotoxic T-lymphocytic (CTLL-2) cell line (Mosley, et al, 1989) and from the human myeloid cell line, TF-1 (Galizzi, et al, 1990). Sequence analysis demonstrated that the IL-4R belongs to the hematopoeitin receptor superfamily.…”
Section: Il-4rmentioning
confidence: 99%